An extension of the theory of planned behavior to predict immediate hedonic behaviors and distal benefit behaviors - Collins, A.; Mullan, Barbara (Pergamon, 2011)
The importance of understanding different behavior types is fundamental to changing patterns of dietary consumption toward optimal health. This study investigates fruit and vegetable (F&V) consumption as a distal benefit behavior and snacking as an immediate hedonic behavior, within the framework of the theory of planned behavior (TPB; Ajzen, 1991). The model was extended to examine the predictive value of past behavior and self-regulatory ability across these two dietary behaviors. A total of 190 undergraduate students from an Australian university were administered two online questionnaires over two measurement points with 1-week interval. At time one, participants completed TPB questionnaires and a behavioral measure of self-regulation. At time two, self-reported dietary behavior was measured. Multiple and hierarchical regression analyses showed that the TPB model significantly predicted intention to perform both dietary behaviors and intention significantly predicted both behaviors. However consistent with hypotheses, there was a large intention-behavior gap and the predictive value of the TPB differed depending on whether the behavior had immediate vs. distal rewards. When past behavior was added to the model, intention was a significant predictor for the hedonic behavior, but not for the distal behavior. Differences in the predictive variables for the two behavior types suggest that the distal benefit behavior vs. immediate hedonic behavior distinction may be useful when designing interventions by considering the temporal element of health decision-making.